Who Banned The War Game? A Fifty-Year Controversy Reassessed. Issue 1 (January 2017) - Cook, John R.
Abstract : The War Game (BBC TV, 1965), directed by Peter Watkins, is one of the most famous films from the 1960s. Banned from TV for twenty years, it gained a limited cinema release which saw it go on to win an Oscar in 1967. Suspicions have long circulated that the BBC's decision to ban the film from TV arose as a result of pressure from government amid fears of the effect that Watkins' documentary dramatisation of a nuclear attack on the UK might have on mass TV audiences. On the fiftieth anniversary of the censorship of the film, this article takes a fresh look at the controversy, examining previously classified Cabinet Office papers and tracing in greater detail than ever before how ministers and civil servants working for Harold Wilson's 1964–70 Labour government reacted to and dealt with the issue. From this evidence, the article argues that the TV censorship of The War Game involved a complex interaction between civil servants in Whitehall, government ministers, including Prime Minister Harold Wilson himself, the Director-General of the BBC and the Chairman of the BBC Board of Governors. The article traces the close relationship between Whitehall and the upper echelons of the BBC during this Cold War period, and argues that The War Game offers a very interesting historical case study which raises disturbing questions both about the limits of the BBC's professed liberalism of the 1960s and about the true extent of its much-vaunted independence from government. The latter is particularly important in the light of more recent and current threats to that independence.